Development of Capcut Application in Natural and Social Science Learning for Elementary School - Holisah, Holisah; Atikah, Cucu; Rusdiyani, Isti (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This development aims to create learning media using the CapCut application for Natural and Social Sciences subjects. The research method used is Research and Development (R&D), which refers to the 4D development model. There are four stages of development: define, design, develop, and disseminate. Data collection was carried out using a questionnaire and a test. Questionnaires were given to the subject and media experts to test the feasibility of learning media products based on the CapCut application. While the primary data source comes from class IV Science textbooks at SDN Kedaleman III and secondary data sources come from class IV students at SDN Kedaleman III. The population in this study were all fourth-grade students at SDN Kedaleman III, totaling 32 students. The sampling technique used a saturated sample; the entire population became the research sample because of the small population. Hence, the sample in this study was students of class IV at SDN Kedaleman III, totaling 32 students. This study used data analysis techniques t-test, namely paired sample t-test. The study results show that the CapCut application-based learning media is very suitable for science learning because it gets high marks from subject and media experts. The material expert's assessment was 89%, and the media expert's assessment was 93% which was classified as very feasible. And the t-test shows that there is a significant difference between the student's pre-test and post-test. Therefore it can be concluded that the CapCut application-based learning media is effectively used in science learning.